A Comparative Study of sFt-1 and Prolactin Levels in Peripartum Cardiomyopathy Patients With and Without Preeclampsia - Triwedya Indra Dewi; Faris Dwiki Adithya; Chaerul Achmad; Sanny Nurfitrica; Hawani Sasmaya Prameswari (Jurnal Kardiologi Indonesia, 2026)
Introduction: Peripartum Cardiomyopathy (PPCM) is a type of heart failure that occurs from late pregnancy to the early postpartum period. While the exact etiology of PPCM remains unclear, several risk factors, including preeclampsia, have been identified. It is hypothesized that PPCM with and without preeclampsia may involve distinct pathophysiological mechanisms, which could be reflected in differences in biomarker levels. This study aims to explore this hypothesis by comparing prolactin levels between PPCM patients with and without preeclampsia. Methods: This observational analytical study employed a cross-sectional design. The study population consisted of PPCM patients registered at Dr. Hasan Sadikin Hospital, Bandung, from September 2018 to June 2024. Subjects were classified into two groups: PPCM with preeclampsia and PPCM without preeclampsia. Soluble Fms-Like Tyrosine Kinase-1 (sFlt-1) and prolactin levels were measured at the time of PPCM diagnosis. Results: A total of 66 patients were included in the final analysis (43 with PPCM and preeclampsia and 23 without preeclampsia). Patients with PPCM and preeclampsia had higher sFlt-1 levels than patients with PPCM without preeclampsia (128.1 [Interquartile Range (IQR) 90.8–279.5] vs. 94.9 [IQR 82.7–110.6] pg/ml; p = 0.046), while prolactin levels did not differ significantly between two groups (36.52 [15.59–88.58] vs. 22.11 [12.69–44.25] ng/ml; p = 0.176). In the PPCM group with preeclampsia, 44.2% (p = 0.002) of patients had elevated levels of both sFlt-1 and prolactin, while none of the subjects without preeclampsia exhibited this combination. Conclusion: sFlt-1 levels are higher in PPCM with preeclampsia, whereas prolactin levels do not differ significantly between the two groups.